Lean body mass and stroke volume, a sex issue - Bertil Delsaut; Anissa Abderrakib; Noémie Ligot; Gilles Naeije (Frontiers in Neurology, 2025)
IntroductionLarge vessel occlusions (LVO) account for over 60% of stroke-related mortality and disability. Lean body mass (LBM) represents metabolically active body tissue and has been associated with reduced mortality. This study aimed to investigate whether body composition influences LVO stroke perfusion volumes and whether this effect is sex-specific.MethodsData were retrospectively collected from all patients admitted between January 2017 and January 2022 with LVO ischemic stroke at the Erasmus Hospital (Brussels), for whom anthropometric and perfusion data were available. Body mass index (BMI) and LBM were calculated using, respectively, the Quetelet’s and the James’ formula. Correlations between body composition and stroke volumes were investigated using Spearman correlations.ResultsA total of 152 patients were included in this study. Mean age 72 ± 14y, female ratio 62.5%, core volume 26 ± 38 mL, penumbra volume 104 ± 61 mL. LBM correlated significantly with stroke volumes (penumbra and core) in the entire group (core: p = 0.001; penumbra: p = 0.001). There was a significant sex-effect, with a significant correlation observed only in women (core: p = 0.008; penumbra: p = 0.007). BMI did not correlate with perfusion volumes at the group level nor at the sex-level.ConclusionLBM significantly impacts LVO stroke volumes, but this effect is observed only in women. LBM may serve as a superior indicator of body composition compared to BMI.